Impact of UK National Health Service smoking cessation services: variations in outcomes in England. Issue 3 (4th September 2003) - Bauld, L; Chesterman, J; Judge, K; Pound, E; Coleman, T
Abstract : Objectives: To determine the extent to which UK National Health Service (NHS) smoking cessation services in England reach smokers and support them to quit at four weeks, and to identify which service and area characteristics contribute to observed outcomes. Design: Ordinary least squares regression was used to investigate local smoking outcomes in relation to characteristics of health authorities and their smoking cessation services. Setting: 76 health authorities (from a total of 99) in England from April 2000 to March 2001. Main outcome measures: Reach —number of smokers attending cessation services and setting a quit date as a percentage of the adult smoking population in each health authority. Absolute success —number of smokers setting a quit date who subsequently reported quitting at four weeks (not having smoked between two and four weeks after quit date). Cessation rate —number of smokers who reported quitting at four weeks as a percentage of those setting a quit date. Loss —percentage lost to follow up. Results: A range of service and area characteristics was associated with each outcome. For example, group support proved more effective than one to one interventions in helping a greater proportion of smokers to quit at four weeks. Services based in health action zones were reaching larger numbers of smokers. However, services operating in deprived communities achieved lower cessation rates than those in more prosperous areas. Conclusions: Well developed, evidence based NHS smoking cessation services, reflecting good practice, are yielding positive outcomes in England. However, most of the data are based on self reported smoking status at four weeks. It will be important to obtain validated data about continuous cessation over one year or more in order to assess longer term impact.